Adolescents’ Unhealthy Eating Behavior and Customer Engagement on Social Media in Sub Urban Areas - Elia Nur A'yunin; Mustakim Mustakim; Imas Arumsari (Amerta Nutrition)
Background: Social media exposure is one of the effective strategies for digital marketing of food and beverage products in this present era. In addition, adolescents are the dominant users of social media (75.5%), which affects their behavior and health status.